Estimation of Serum Calcium Level among Hospitalised Infants with Acute Bronchiolitis: A Cross-sectional Study - Suman Gupta; Nirmal Kumar; Amardip Kaur; Deepak Kumar Gupta; Shifali Gupta (Journal of Clinical and Diagnostic Research, 2023)
Introduction: Acute bronchiolitis is a common viral respiratory illness with clinical features ranging from mild to severe forms, requiring intensive care management. Calcium, a micronutrient, plays a significant role in numerous intracellular and extracellular events. Vitamin D deficiency is known to be associated with respiratory infections, and vitamin D metabolism regulates serum calcium and Alkaline Phosphatase (ALP) levels. Thus, calcium levels may be the actual causative factor at the molecular level to determine the severity of respiratory infections. Aim: To estimate and compare serum calcium levels in infants with acute bronchiolitis and controls. Additionally, it aimed to investigate the effect of sunlight exposure on calcium levels in infants presenting at a tertiary care centre. Materials and Methods: A cross-sectional study was conducted from October 2004 to April 2006, over two consecutive years, among 446 infants in the paediatric unit of a tertiary care centre in Delhi, North India. A total of 223 infants (<1 year of age) hospitalised with a diagnosis of acute bronchiolitis, presenting with the first episode of wheeze based on American Academy of Paediatrics (AAP) criteria (including coryza, fever, tachypnoea, tachycardia, paroxysmal wheezy cough, and irritability), were considered as cases. An equal number of age-matched controls (n=223), admitted for non respiratory illnesses, were included. Blood samples were collected for total serum calcium, phosphorus, and ALP, along with other relevant investigations related to their diagnosis. Statistical analysis was performed using Student’s t-test, Kruskal-Wallis’s test, and Chi-square test. Results: The study included 223 patients in both the case and control groups. In the control group, there were 76.58% males and 23.42% females, while in the cases, there were 81.53% males and 18.47% females. The mean age of cases was 5.78±3.45 months, and controls were 4.77±2.83 months, with a mean difference of 1.01 (95% CI, 0.42-1.59). The mean calcium levels were 9.00±1.43 mg/dL and 8.71±1.51 mg/dL in controls and cases, respectively, with a mean difference of 0.29 (95% CI0.02 to 0.56), which was statistically significant (p-value=0.037). There was no significant difference in phosphorus and ALP levels between the two groups. Conclusion: This study found an association between calcium levels and acute bronchiolitis. The findings suggest that low serum calcium levels might serve as a risk factor for acute bronchiolitis.